Delving into a translator’s journey of translating marginalised voices of Bengal: An insightful discussion with V. Ramaswamy - Pal, Bidisha; Rahman, Mojibur (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2023)
This interview discussion is the outcome of a virtual meeting partially along with email correspondence. In this interview discussion with Bidisha Pal and Md. Mojibur Rahman, translator V. Ramaswamy focuses on the journey of his translation and tryst with the marginalised Dalit voice(s) in Bengal. He speaks about the writings that propel him to choose translating and to carry voice(s) beyond the Bengal arena, thus dissolving language barriers. The deliberate choice to translate various pieces representing various time periods acts as a witness to his existence as an independent translator. According to him, translation is also a source of healing to deal with a tragic past and the complicacies that life often presents to him. He shares his experience translating Subimal Mishra, the powerful poet who speaks for marginalised people. Ramaswamy, as he states in the interview, makes a vow to translate Mishra’s whole writing career. He talks about translating Manoranjan Byapari, a Bengali Dalit prize-winning author and political persona who has also championed the Dalit cause in Bengal, Adhir Biswas, the story-writer and publisher of a publishing house in Kolkata Gangchil that publishes writings by those literary personas who do not fall, as such, into the category of the mainstream, Bangladeshi writer Shahidul Zahir whose revolutionary voice and zeal reverberate in the literary world of Bangladesh, as well as Ansaruddin, a writer and farmer by profession whose works Ramaswamy is currently translating. Despite not being a part of the literary world as such, Ramaswamy has built an intense connection with literature and has gradually become part of the world. For him, translation is something that has to remain faithful to the source text especially if people are doing literary translation.